Europa alleine verteidigen? Mit Anstrengung möglich, aber teuer - Maximilian Dambacher; Martin Bader; Marcus Matthias Keupp (Wirtschaftsdienst, 2025)
– Europe can no longer rely on the United States for its defence but is currently lacking essential capabilities to assure security itself. European countries should not give up on NATO but seek to close capability gaps by developing the European defence industrial base. The EU can play an important role in helping European countries overcome fragmentation in the defence industry, reduce dependencies on other actors and enable financing. In the short term, debt seems the only viable method to pay for quick rearmament - but this includes evident risk. Moreover, the ease of mobilising funds for defence and the urgency to do so vary greatly in Europe.
Keywords: F50; H60; N40; 330; Militärausgaben; Militärpolitik; Militärbündnis; Europa; Militärausgaben; Militärpolitik; Militärbündnis; Europa